Spin selectivity in chiral metal–halide semiconductors. Issue 45 (16th November 2021) - Feng, Tanglue; Wang, Zhiyu; Zhang, Zixuan; Xue, Jie; Lu, Haipeng
Abstract : This minireview elaborately presents the spin selectivity of chiral metal–halide semiconductors in photonic/electronic processes, and their applications in optoelectronic/spintronic devices, with the structure–property relationship highlighted. Abstract : Controlling the spin states of freedom represents a significant challenge for the next-generation optoelectronic and spintronic devices. Chiral metal–halide semiconductors (MHS) have recently emerged as an important class of materials for spin-dependent photonic and electronic applications. In this Minireview, we first discussed the chemical and structural diversity of chiral MHS, highlighting the chirality formation mechanism. We then provided our current understanding on the spin-sensitive photophysical and transport process with a focus on how chirality enables the spin selectivity in chiral MHS. We summarized recent progress on the experimental demonstration of spin control in various photonic and spintronic devices. Finally, we discussed ongoing challenges and opportunities associated with chiral MHS.